p53 dosage can impede KrasG12D- and KrasQ61R-mediated tumorigenesis. - Özgün Le Roux; Jeffery I Everitt; Christopher M Counter (PLoS ONE)
Mice engineered with a G12D versus Q61R mutation in Kras exhibited differences in tumorigenesis. Namely, the incidence or grade of oral or forestomach squamous epithelial lesions was more prevalent in the KrasG12D background while hematolymphopoietic disease was more prevalent in the KrasQ61R background. Loss of the Trp53 gene encoding the tumor suppressor p53 enhances the ability of oncogenic Kras to initiate tumorigenesis in carcinogen and genetic models of lung cancer. Conversley, an extra copy of Trp53 (Super p53) was recently shown to suppress Kras-induced tumorigenesis in a genetic model of this disease. Given this, we evaluated whether an extra copy of Trp53 would alter tumorigenesis upon global activation of a modified Kras allele engineered with either a G12D or Q61R mutation. We report that an increase in p53 dosage significantly reduced the incidence or grade of oral and forestomach squamous tumors induced by either G12D and Q61R-mutant Kras. The incidence of myeloproliferative disease was also significantly reduced with increased p53 dosage in the KrasQ61R background. Both the percentage of mice with lung tumors and total number of adenomas per animal were unchanged. However, the incidence and grade of peripheral atypical alveolar hyperplasia was significantly decreased in both backgrounds with increased p53 dosage. Finally, the number of foci of bronchioloalveolar hyperplasia per animal significantly increased with increased p53 dosage in the KrasG12D background. These results suggest that an extra copy of p53 can impede oncogenic Kras driven tumorigenesis in some tissues.